FORMULASI DEVELOPMENT INDEX UNTUK OPTIMASI RENCANA PENGEMBANGAN INSTITUSI PENDIDIKAN TINGGI - Prasetyo, Suseno Budi (JURNAL TEKMAPRO, 2006)
ABSTRACT To face the change, which happens in both inside and outside the education system, we need development planning at the education system, specially the higher education system. The aim of this research is to optimize the development planning at the higher education system using development index formulation. The development planning is made based on the identification of business processes, sub business processes, activities, root causes and alternative solutions. The management weights the results of identification process. Then, the development index formulation is created based on the results of management decision. The development index formulation is limited by the resource of the organization.Â  The next step of this research is optimizing the formulation using integer linear programming. Finally, the higher education institution uses the result of the optimization process to create the development planning appropriate with the resource they have. From the result of case study in Department âXâ, there are 4 program which is appear after the optimizing process, consists of sending 30 lecturers to the workshop, 2 times lecture notes competition, 4 times coordination and evaluation program, and 2 times survey to the students. Keywords: development planning, development index, integer linear programming ABSTRAK Untuk menghadapi perubahan yang terjadi, baik di dalam sistem pendidikan maupun lingkungan di luar sistem pendidikan, dibutuhkan rencana pengembangan (development planning) pada sistem pendidikan, terutama pendidikan tinggi. Dalam penelitian ini, dilakukan upaya optimasi terhadap rencana pengembangan institusi pendidikan tinggi, dengan menggunakan formulasi development index. Rencana pengembangan dibuat berdasarkan identifikasi proses bisnis, sub proses bisnis, aktifitas, root cause dan alternatif solusi. Hasil identifikasi tersebut dibobotkan oleh pihak manajemen terkait. Dari hasil pembobotan terhadap seluruh proses bisnis, dibuat persamaan developmet index. Nilai developmet index dibatasi oleh constrains berupa resource yang dimiliki organisasi. Dengan menggunakan integer linear programming, dilakukan maksimalisasi terhadap nilai developmet index, sehingga pihak institusi pendidikan tinggi akan mendapatkan sebuah rencana pengembangan yang optimal sesuai dengan kapasitas resource yang dimiliki. Dari studi kasus yang diterapkan pada Program Studi âXâ, terdapat 4 kegiatan yang muncul berdasarkan hasil optimasi, yaitu pengiriman dosen untuk mengikuti workshop sebanyak 30 dosen, 2 kali kompetisi pembuatan buku ajar, 4 kali kegiatan koordinasi dan evaluasi, serta 2 kali penyebaran kuesioner kepada mahasiswa. Â  Kata kunci: development planning, development index, integer linear programming